Chromium bioremediation of batik industrial wastewater using a consortium of sulfate-reducing bacteria from forested wetland soil - La Ode Muhamad Syawaluddin; Endah Retnaningrum (Journal of Degraded and Mining Lands Management, 2022)
Chromium pollutants in textile wastewater can be removed by bioremediation using sulfate-reducing bacteria (SRB) from forested wetland soil. Biostimulation of carbon sources in the form of molasses and a supporting material in the form of zeolite to trap bacteria and create biofilms can improve the ability of SRB to bioremediate chromium. The batch bioremediation technique was further examined by including molasses, a combination of molasses and zeolite, and SRB, which has been adapted to acclimatize wastewater that is diluted two times. Adaptive SRB aged 7 days, which had reached the exponential growth phase, showed optimal bioremediation activity when molasses and zeolite were added. Results of further observations of the consortium on continuous bioremediation with the same treatment showed decontamination of chromium efficiency that reached about 94%. In addition, pH values decreased efficiency at approximately 7.3 in 14 days of incubation. The biological oxygen demand, chemical oxygen demand, and sulfate concentrations also decreased at around 89%, 92%, and 91%, respectively. SRB immobilization with zeolite-induced biofilm formation was observed at 9 days, and it further increased at 14 days. SRB cells observed were attached to the surface of the zeolite, between cells connected to each other by extracellular polymeric substances. The mass of sulfur and chromium on the surface of the zeolite increased from the 9th and 14th days. Sulfur increased from 0.07% to 0.27%, whereas chromium increased from 0.21% to 0.84%. The increase in the percentage of the two elements on the zeolite surface indicated the decontamination of sulfate and chromium pollutants in wastewater.